2021
DOI: 10.1136/jitc-2020-002303
|View full text |Cite
|
Sign up to set email alerts
|

Early toxicity and clinical outcomes after chimeric antigen receptor T-cell (CAR-T) therapy for lymphoma

Abstract: BackgroundChimeric antigen receptor T-cell (CAR-T) infusion is associated with early toxicity. Yet, whether early toxicity development holds ramifications for long-term outcomes is unknown.MethodsFrom a large cohort of consecutive adult patients treated with CAR-T therapies for relapsed or refractory lymphomas from 2016 to 2019, we assessed progression-free survival (PFS), by toxicity development (cytokine release syndrome (CRS), neurotoxicity, or cardiotoxicity]. We also assessed the relationship of toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Nonetheless, these observations complement an emerging body of research evaluating the link between the severity of clinician-reported toxicities and patients’ clinical outcomes. For example, Brammer and colleagues found that patients with lymphoma who developed moderate (grade 2) CRS post-CAR-T infusion had better disease response than patients with mild (grade 1) or severe (grade 3) CRS [ 48 ]. Future studies should combine clinician-reported toxicities with other data sources, such as PROs, to identify early risk factors for suboptimal clinical outcomes [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, these observations complement an emerging body of research evaluating the link between the severity of clinician-reported toxicities and patients’ clinical outcomes. For example, Brammer and colleagues found that patients with lymphoma who developed moderate (grade 2) CRS post-CAR-T infusion had better disease response than patients with mild (grade 1) or severe (grade 3) CRS [ 48 ]. Future studies should combine clinician-reported toxicities with other data sources, such as PROs, to identify early risk factors for suboptimal clinical outcomes [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have specifically reported the cardiovascular outcomes of CAR-T therapy. However, reporting remains heterogeneous, warranting a standardization of methods and endpoints to allow a detailed comparison in future studies [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] ( Table 3 ).…”
Section: Results Of Clinical Investigationsmentioning
confidence: 99%
“…Studies have been performed in both adult and pediatric cohorts, with a mean sample size of about 100 patients in more recent series [ 4 , 12 , 20 , 21 , 26 , 29 , 33 , 34 ]. The most reported and frequent complication is hypotension requiring inotropic support, affecting about 25–30% of pediatric patients and 10% of adult patients [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Left ventricular systolic dysfunction affects 5–10% of patients, but its proper assessment is still debated.…”
Section: Results Of Clinical Investigationsmentioning
confidence: 99%
“…Due to various challenges of external environment, such as immune surveillance and treatment pressures, CCs generally evolve and develop a low immunogenicity for escaping recognition by immune cells, such as dendritic cells (DCs) and T lymphocytes ( 3 - 6 ). Incidentally, an improved disease-free survival is observed in cases where tumors have low immune evasion capacity and a uniformly high infiltration of immune cells, or where tumor cells do not present any evidence of DNA immunoediting or disruption to antigen presentation ( 7 - 9 ). Hence, it remains a formidable challenge to compel CC-specific dying through reprogramming intrinsic immunogenicity during cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%